(* Basis[5]={d[10],d[26],d[31],d[36]} *) d[1]=CD[1,2,3,4,5,1,2,3,4,5] 4d[10]-2d[26] d[2]=CD[1,2,3,4,1,5,2,4,3,5] 4d[10]-4d[26]-2d[31]+4d[36] d[3]=CD[1,2,3,4,1,5,2,3,4,5] 4d[10]-3d[26]-2d[31]+3d[36] d[4]=CD[1,2,3,1,4,3,5,4,2,5] d[10]-2d[26]+4d[31]-2d[36] d[5]=CD[1,2,3,1,4,5,3,2,5,4] 2d[10]-2d[26]-d[31]+2d[36] d[6]=CD[1,2,3,1,4,5,3,2,4,5] 2d[10]-d[26]-2d[31]+3d[36] d[7]=CD[1,2,3,1,4,5,2,3,5,4] 2d[10]-2d[26] d[8]=CD[1,2,3,1,4,5,2,3,4,5] 2d[10]-d[26] d[9]=CD[1,2,3,1,4,2,5,4,3,5] d[10]-d[26]+2d[31]-d[36] d[10]=CD[1,2,3,1,4,2,5,3,4,5] d[10] d[11]=CD[1,2,3,1,2,4,5,3,4,5] 4d[31]-4d[36] d[12]=CD[1,2,1,3,4,5,3,5,2,4] d[31] d[13]=CD[1,2,1,3,4,5,3,4,2,5] 2d[31]-d[36] d[14]=CD[1,2,1,3,4,5,3,2,5,4] d[26]-d[31]+d[36] d[15]=CD[1,2,1,3,4,5,3,2,4,5] d[26] d[16]=CD[1,2,1,3,4,5,2,5,4,3] d[31]-2d[36] d[17]=CD[1,2,1,3,4,5,2,4,5,3] 2d[31]-3d[36] d[18]=CD[1,2,1,3,4,5,2,5,3,4] 2d[31]-3d[36] d[19]=CD[1,2,1,3,4,5,2,4,3,5] d[26]-d[36] d[20]=CD[1,2,1,3,4,5,2,3,5,4] d[26]-d[36] d[21]=CD[1,2,1,3,4,5,2,3,4,5] d[26]+2d[31]-3d[36] d[22]=CD[1,2,1,3,4,2,5,4,5,3] d[31]-d[36] d[23]=CD[1,2,1,3,4,2,5,4,3,5] d[26]-d[31]+d[36] d[24]=CD[1,2,1,3,4,2,4,5,3,5] d[31]-d[36] d[25]=CD[1,2,1,3,4,2,5,3,5,4] 2d[31]-2d[36] d[26]=CD[1,2,1,3,4,2,5,3,4,5] d[26] d[27]=CD[1,2,1,3,4,2,3,5,4,5] 2d[31]-2d[36] d[28]=CD[1,2,1,3,2,4,5,4,3,5] d[31] d[29]=CD[1,2,1,3,2,4,5,3,5,4] d[31]-d[36] d[30]=CD[1,2,1,3,2,4,5,3,4,5] 2d[31]-d[36] d[31]=CD[1,2,1,3,2,4,3,5,4,5] d[31] d[32]=CD[1,2,1,2,3,4,5,4,5,3] 0 d[33]=CD[1,2,1,2,3,4,5,4,3,5] d[36] d[34]=CD[1,2,1,2,3,4,5,3,5,4] d[36] d[35]=CD[1,2,1,2,3,4,5,3,4,5] 2d[36] d[36]=CD[1,2,1,2,3,4,3,5,4,5] d[36]